2022
DOI: 10.1088/1755-1315/1068/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of erosion on the mechanical composition and physical properties of serozems on rainfed soils, Tashkent province, Uzbekistan

Abstract: The problem of soil protection from erosion is relevant for many countries in the arid zone of the world, including the territory of Uzbekistan. In the republic, the main arrays of crops are located on rainfed lands, where the crop is created only due to moisture in precipitation. The amount of porosity (duty cycle) of soils is determined mainly by specific and bulk mass, mechanical composition, and humus content. Porosity of soils decreases from unwashed soils to washed away and down the profile. In the arabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The results of our practical studies carried out in the Syrdarya basin (Fergana Valley, Hungry Steppe, South Kazakhstan, and Kyzylorda regions) showed that the sanding process is typical for vertical drainage wells and "on water", but not for all of them [6][7][8][9][10].…”
Section: Construction Of Water Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our practical studies carried out in the Syrdarya basin (Fergana Valley, Hungry Steppe, South Kazakhstan, and Kyzylorda regions) showed that the sanding process is typical for vertical drainage wells and "on water", but not for all of them [6][7][8][9][10].…”
Section: Construction Of Water Wellsmentioning
confidence: 99%
“…These include such scientists as S. Averyanov, A. Mikhaltsevich, A. Eskov, A. Yangol, and N. Reshetkina. In Uzbekistan, a special place is occupied by scientists in the operation of vertical drainage wells, as well as the restoration of flow rates of vertical drainage wells M. Yakubov, A. Abirov, A Umarov, Z. Pushkarev, V. Nasonov, I. Akhmedov, Z. Mirkhasilova, A.Khojiyev, R.Muradov and others [1,2,3,4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of groundwater in Karakalpakstan, in recent years, due to an increase in the concentration of mineralization and general hardness, also does not meet the requirements of the standard for sources of domestic and drinking water supply [17,18].…”
Section: Introductionmentioning
confidence: 99%